Peningkatan Literasi Keuangan Syariah melalui Sosialisasi di Desa Cibatu - Sukron Mamun; MH Ainulyaqien; Sakum; Nenda; Siti Juariah (DPPM Universitas Pelita Bangsa, 2021)
Islamic finance plays an important role in the Indonesian economy. A national survey conducted by the Financial Services Authority (OJK) in 2016 showed that the level of public awareness and adoption of Islamic financial products and services is still low. This can be seen from the low Islamic Financial Literacy Index, reaching 8.11%, and the Islamic Financial Inclusion Index, reaching 11.06%. Thus, financial knowledge of Islam enables individuals to understand and apply the concept of Islamic finance to effectively manage their funds in accordance with Islamic principles.This research adopts qualitative methods based on raw data, namely interviews, triangulation analysis techniques of lectures, simulations, follow-up, and evaluation. From the evaluation results, it can be interpreted that the training activities to increase the literacy of Islamic financial institutions in Indonesia have had a positive impact on the local community in improving financial literacy related to Islamic financial institutions. Participants provide suggestions and input that can be the basis for improving and improving the quality of future service programmes. The service team can conduct regular follow-ups to ensure that the improvement of financial literacy continues and the community can apply the knowledge they have gained in their daily lives. this training has a positive impact on the local community in improving financial literacy related to Islamic financial institutions.